Screening of Cervical Cancer by Conventional Papanicolaou Smear and a Liquid-Based Thin-Layer (Thin Prep) Smear - Fuangkaew, Aphinya; Suthutvoravut, Somsak; Patrachai, Sanya; Singhakajen, Vachira (Ramathibodi Medical Journal, 2009)
Objectives: To study the rate of cervical cancer screening in women and its results comparing between conventional Papanicolaou smear (Pap smear) method and Thin Prep smear method. Material and Method: This is a descriptive study that analysis of the women who visited the gynecological out patient department (OPD) clinic of a private hospital in Bangkok, Thailand. The cervical cancer screening was done by conventional Papanicolaou smear (Pap smear) or Thin Prep smear. The rate of screening and results of abnormal findings were reported. Data was collected from gynecological OPD medical records during April to December, 2007. Results: The results showed that among 5,943 women who came to a gynecological OPD clinic, 59.7%, (95% CI = 58.4, 60.9) were screened for cervical cancer, abnormalities were found in 31 women, 0.87%, (95%CI = 0.57, 1.18). The cervical cancer screening by Thin Prep found 5.8 times more abnormalities than by Pap smear (p < 0.05). Abnormalities were found by Thin Prep in 26 cases (1.56%) compared to 5 cases (0.27%) by Pap smear. Eighty percent of abnormal Pap smear results correlated with pathological diagnoses (4 out of 5 cases) compared to 77% (17 out of 22 cases) of Thin Prep. Significant factors associated with cervical cancer screening were age, occupation, marital status, number of living children and residence. Significant factors associated with the screening method were age, occupation, marital status and number of living children (p < 0.05). Conclusion: The rate of cervical cancer screening in private hospitals was still less than expected. The Thin Prep smear method found more abnormal cervical cells than the Pap smear method but with comparable accuracy. This study could be useful in order to encourage a more appropriate screening method for women.